Mesulergine in early Parkinson's disease: a double blind controlled trial. Issue 4 (April 1986) - Dupont, E; Mikkelsen, B; Jakobsen, J
Abstract : The efficacy and tolerance of treatment with an 8-alpha-amino-ergoline derivative CU32-o85, Mesulergine, were compared with levodopa/benserazide (Madopar) in a 3 month double-blind controlled trial in 31 patients with Parkinson's disease, not previously treated with levodopa. The two treatments were equally well tolerated, and neither dyskinesias nor dose-related fluctuations developed. In 90% of the patients treated with Mesulergine, Parkinsonian symptoms improved, and at the dose given the overall therapeutical response was two-thirds that of levodopa. During further 9 months of open study the beneficial effect was maintained equally well in both groups. Compared with other dopamine agonists Mesulergine has a considerable antiparkinsonian effect. Unfortunately, further clinical evaluation of the compound recently has been stopped owing to sex and species specific histological alterations in rats. It is suggested that Mesulergine derivatives might well be of value in future treatment of early Parkinson's disease and of late incompensated stages.